NPS detection in prison: A systematic literature review of use, drug form, and analytical approaches - Amira Guirguis (Drug Testing and Analysis, 2022)
This paper presents a systematic literature review on the detection of new psychoactive substances (NPS) in prison settings. It includes the most frequently reported NPS classes, the routes and forms used for smuggling, and the methods employed to analyse biological and non-biological samples. The search was carried out using MEDLINE (EBSCO), Scopus (ELSEVIER), PubMed (NCBI), and Web of Science (Clarivate) databases, along with reports from the grey literature in line with the PRISMA-S guidelines. A total of 2708 records were identified, of which 50 met the inclusion criteria. Findings showed the most prevalent NPS class reported in prison was synthetic cannabinoids (SCs). The most frequently reported SCs in non-biological samples were 4F-MDMB-BINACA, MDMB-4en-PINACA, and 5F-ADB. These were smuggled mainly through the postal services deposited on paper or herbal matrices. Concentrations of SCs detected on seized paper ranged between 0.05 and 1.17 mg/cm2. The SCs most frequently reported in biological specimens (i.e., urine, blood, saliva, and wastewater) were 5F-MDMB-PICA, 4F-MDMB-BINACA, and MDMB-4en-PINACA. Concentrations of SCs reported in femoral blood and serum were 0.12–0.48 ng/ml and 34–17 ng/ml, respectively. Hyphenated techniques were predominantly employed and generally successful for the detection of NPS in biological (i.e., LC-HRMS/MS) and non-biological samples (i.e., LC-HRMS/MS and GC–MS). The onsite technique IMS showed promise for detecting SCs in various forms; however, immunoassays were not recommended. Future work should focus on accurate in-field detection of SCs deposited on paper and in urine and saliva to improve real-time decision-making, as well as wastewater and air monitoring for overall drug use trends.